Management of Regional Natural Resources based on the Variability of Environmental and Economic Indicators - Semyachkov, Aleksandr I.; Gao, Rong; Atamanova, Elena A. (Economy of Regions, 2021)
Major ecological problems encourage regional authorities to find a balance between the consumption of natural resources and the preservation of the environment. To this end, we assessed environmental management in three Russian regions (the Ural, Siberian and Far Eastern Federal Districts) in the period 1990-2018 using temporal variability analysis of ecological and economic indicators. Based on the spatial and temporal variability and time series analysis, we developed a methodology for examining the use of natural resources and occurring violations. Temporal variability of environmental and economic indicators was visualised for each type of natural resources (atmospheric, water, forest and land). Additionally, the proposed method allowed us to identify a trend towards balanced environmental management and restoration of regional natural resources over a long period. The variability of environmental and economic indicators of 27 constituent entities of the Russian Federation was analysed based on graphic material. Further, four main groups of these indicators (stable, unstable, homogeneous, and heterogeneous ones) were identified. This typology can be used to determine the leading and outsider regions in terms of the balanced environmental management, indicating its general trend (positive or negative one). Overall, satisfactory and positive environmental management dominate in the examined districts. Simultaneously, negative environmental management (predominance of resource use over their restoration) leads to the adoption of drastic measures to remedy the situation. The obtained results may be useful for developing a methodology to assess environmental and economic indicators of balanced environmental management in regions.